2003
DOI: 10.1038/sj.onc.1206244
|View full text |Cite
|
Sign up to set email alerts
|

Distinct nuclear body components, PML and SMRT, regulate the trans-acting function of HTLV-1 Tax oncoprotein

Abstract: Several viruses target cellular promyelocytic leukemia (PML)-nuclear bodies (PML-NBs) to induce their disruption, marked morphological changes in these structures or the relocation to PML-NB components to the cytoplasm of infected cells. PML conversely interferes with viral replication. We demonstrate that PML acts as a coactivator for the human T-cell leukemia virus type 1 (HTLV-1) Tax oncoprotein without direct binding. Tax was identified within interchromatin granule clusters (IGCs)/RNA splicing bodies (SBs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
0

Year Published

2004
2004
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 49 publications
2
16
0
Order By: Relevance
“…A pharmacological HDAC inhibitor disrupted these subnuclear bodies, suggesting that they are maintained by specific functional interactions (Downes et al, 2000). This concept is supported by the observation that the spherical co-repressor focal bodies are spatially distinct from several other subnuclear protein compartments (Ariumi et al, 2003;Downes et al, 2000;Wu et al, 2001). Using a quantitative imaging approach, we demonstrated that MAD-body formation by NCoR was directly related to expression level (Voss et al, 2004), indicating a highly regulated mechanism controlling focalbody formation or maintenance.…”
Section: Introductionsupporting
confidence: 50%
“…A pharmacological HDAC inhibitor disrupted these subnuclear bodies, suggesting that they are maintained by specific functional interactions (Downes et al, 2000). This concept is supported by the observation that the spherical co-repressor focal bodies are spatially distinct from several other subnuclear protein compartments (Ariumi et al, 2003;Downes et al, 2000;Wu et al, 2001). Using a quantitative imaging approach, we demonstrated that MAD-body formation by NCoR was directly related to expression level (Voss et al, 2004), indicating a highly regulated mechanism controlling focalbody formation or maintenance.…”
Section: Introductionsupporting
confidence: 50%
“…For example, one of the pre-mRNA splicing factors, SC35, appears as 20 to 40 speckles per nucleus (67). The promyelocytic leukemia gene product controlling aspects of apoptosis, cell proliferation, and transcriptional regulation was found within distinct subnuclear bodies, termed promyelocytic leukemia (PML) nuclear bodies (PML-NBs) (3). Some corepressor complexes were localized in distinct subnuclear bodies line, MCF-7, were obtained from American Type Culture Collection (Manassas, VA).…”
Section: Steroid Hormone Receptors Including Estrogen Receptors (Er␣mentioning
confidence: 99%
“…In addition, PML has been shown to modulate Tax function in different contexts (7,41). However, previous findings on the colocalization of Tax with PML remain controversial.…”
Section: Resultsmentioning
confidence: 95%
“…However, previous findings on the colocalization of Tax with PML remain controversial. Although one group has suggested the residence of Tax in PML domains (7), others have also found that Tax and PML are separate (41). To clarify this issue, we costained Tax-expressing cells for Tax and PML.…”
Section: Resultsmentioning
confidence: 99%